2007
DOI: 10.1159/000103226
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Allergy due to the Two-Spotted Spider Mite <i>(Tetranychus urticae)</i> among Table Grape Farm Workers

Abstract: Background: Recent studies have reported an increased prevalence of respiratory symptoms among farm workers. The aim of this study was to identify risk factors associated with spider mite allergy among table grape farm workers. Methods: A cross-sectional study of 207 workers in table grape farms was conducted. Skin prick tests used extracts of 8 common aeroallergens, grape mould (Botrytis cinerea) and Tetranychus urticae. Specific IgE to T. urticae was quantified using ImmunoCAP (Phadia). Erythrocyte cholinest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 48 publications
0
11
1
Order By: Relevance
“…25 In contrast, we found a fair to good agreement between sensitisation to T. urticae and sensitisation to the house-dust mites and A. siro, and a fair agreement between sensitisation to any of the house-dust mites and sensitisation to the storage mites B. tropicalis and A. siro but not the other storage mites. Although spider mite-derived extracts contain allergens that are shared in common with domestic mites, major allergens derived from spider mites are unique in terms of cross-reactivity with domestic mites.…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…25 In contrast, we found a fair to good agreement between sensitisation to T. urticae and sensitisation to the house-dust mites and A. siro, and a fair agreement between sensitisation to any of the house-dust mites and sensitisation to the storage mites B. tropicalis and A. siro but not the other storage mites. Although spider mite-derived extracts contain allergens that are shared in common with domestic mites, major allergens derived from spider mites are unique in terms of cross-reactivity with domestic mites.…”
Section: Discussioncontrasting
confidence: 66%
“…23,24 They have emerged as an important allergen in agricultural workers dealing with fruit trees or working in greenhouses as well as in the surrounding populations, the main symptoms associated with sensitisation and exposure to Tetranychidae mites being rhinoconjunctivitis and asthma. 17,23,25 Jeebhay et al found that T. urticae could be responsible for work-related asthma symptoms in their study of table grape farm workers in the Western Cape and that skin reactivity to T. urticae was more common than to housedust mite. 25 A Korean study found that these mites might be common sensitising allergens in the general adult population and that they may play a role in the manifestation of rhinitis and asthma symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This seemingly frequently encountered cross-reactivity is probably due to tropomyosin and may have significant clinical implications. This has been shown particularly for shellfish allergens and tropomyosins from insects and mites, which are all part of the phylum arthropod [81,82].…”
Section: Between Shellfish and Other Invertebratesmentioning
confidence: 96%
“…This seemingly frequently encountered cross‐reactivity is probably due to tropomyosin and may have significant clinical implications. This has been shown particularly for shellfish allergens and tropomyosins from insects and mites, which are all part of the phylum arthropod [81, 82]. A recent study demonstrated sensitization to shrimp tropomyosin in orthodox Jews, who are prohibited by religious dietary laws from eating shellfish, which could be indicative of sensitization to tropomyosin from non‐crustacean, such as HDM and cockroaches, via the inhalation route [83].…”
Section: Immunoglobulin‐e Cross‐reactivity Of Shellfish Allergensmentioning
confidence: 99%